IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 TERHADAP SEKTOR PENGUPAHAN - Irayadi (The Juris, 2022)
Wages are all kinds of payments arising from an employment contract, regardless of the type of work and denomination. Wages are income received by workers which is a reward for the work that has been done. Legal arrangements related to wages have been regulated in Law Number 13 of 2003 concerning Manpower and Government Regulation Number 78 of 2015 concerning Wages. However, over time, these legal arrangements have changed. One of them is the establishment of a new regulation, namely Law Number 11 of 2020 concerning Cipa Kerja. The judicial review of the law was carried out by the Constitutional Court in November 2021, the Constitutional Court (MK) had read out Decision Number 91/PUU-XVIII/2020 regarding the submission of judicial review from several parties regarding Law Number 11 of 2020 concerning Job Creation ( Job Creation Law). The research method uses normative legal methods, sources of legal materials include primary, secondary and tertiary legal materials. The technique of collecting legal materials uses literature study and the technique of analyzing legal materials uses descriptive qualitative techniques. The results of the study show that the Constitutional Court’s Decision Number 91/PUU-XVIII/2020 related to the judicial review of the Job Creation Law on the Wage Sector has had extraordinary legal impacts in the aspects of legislation and administration. Regarding the wage sector, in this case the Job Creation Law abolishes, changes and introduces new regulations regarding wages. If the Manpower Law only recognizes the type of minimum wage, then Article 88B of the Job Creation Law contains the concept of wages with units of time and results based on hours. The abolition of the sectoral minimum wage resulted in no difference in wages adjusted to the specifications of expertise per sector.